Penguatan Akidah Anak YDSI Subulus Salaam Desa Kebonrejo Kepung Melalui Pembiasaan Membaca Aqoid 50 - Ahmad Kafi Husain; Muhammad Faiz Amiruddin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
In the Islamic creed there is a so-called aqoid 50 which details are: 20 obligatory nature of Allah, 20 impossible nature of Allah, 1 nature of Allah jaiz, 4 obligatory nature of the apostles, 4 impossible nature of the apostles, and 1 nature of jaiz of the apostles. These 50 aqoids are now being forgotten by Muslims so it is not uncommon to meet a Muslim who feels unfamiliar with aqoid 50. And that's why this program is implemented. By teaching and familiarizing the children of YDSI Subulus Salaam Kebonrejo Village to read, memorize, and understand aqoid 50, this program has minimized the possibility of children of YDSI Subulus Salaam Kebonrejo Village will not know about aqoid 50 and add their insights related to the science of faith so that later they will have a strong creed and not easily falter.